Atom search optimization and its application to solve a hydrogeologic parameter estimation problem - Zhao, Weiguo; Wang, Liying; Zhang, Zhenxing (Knowledge-based systems, 2019)
In recent years, various metaheuristic optimization methods have been proposed in scientific and engineering fields. In this study, a novel physics-inspired metaheuristic optimization algorithm, atom search optimization (ASO), inspired by basic molecular dynamics, is developed to address a diverse set of optimization problems. ASO mathematically models and mimics the atomic motion model in nature, where atoms interact through interaction forces resulting from the Lennard-Jones potential and constraint forces resulting from the bond-length potential. The proposed algorithm is simple and easy to implement. ASO is tested on a range of benchmark functions to verify its validity, qualitatively and quantitatively, and then applied to a hydrogeologic parameter estimation problem with success. The results demonstrate that ASO is superior to some classic and newly emerging algorithms in the literature and is a promising solution to real-world engineering problems. •A novel optimization algorithm called Atom Search Optimization (ASO) is proposed.•ASO is benchmarked on 37 well-known test functions.•The results on test functions show the competitiveness of ASO.•The results on hydrogeologic parameter estimation confirm the performance of ASO.